Supply chain integrity - Mukucha, Paul (Logistics, supply chain, sustainability and global challenges, 2025)
Ethics has become a trending phenomenon in most disciplines as a result of the sustainability wave enshrined in the United Nations Sustainability Goals (SDGs). In business circles procurement ethics have become topical as a result of the rising malpractices whose ripple effects have far reaching economic, social and environmental consequences. In the agricultural supply chains procurement ethics have been called to question due to outcries from the tobacco contract farmers whose livelihoods are affected by supplier development washing in the form of exorbitantly priced contract farming inputs. The unethical practice of supplier development washing in the form of exorbitantly priced tobacco contract farming inputs has some ripple effects which this study sought to determine. Twenty-five contracted tobacco farmers were interviewed and the results indicated that farmers subjected to tobacco merchants’ unethical conduct tend to practice contractor switching, side marketing, become insolvent, and indulge in unorthodox cost cutting measures. The study recommended that the regulatory authorities should intervene to bring sanity to the tobacco supply chains through enforcing contract farming mechanisms that reflect genuine supplier development.
Keywords: deontologija; etika nabave; information and communication technology; kontaktno kmetovanje; razvoj dobaviteljev; SMEs and material requirement planning; supply chain efficiency